Health Benefits of β-Hydroxy-β-Methylbutyrate (HMB) Supplementation in Addition to Physical Exercise in Older Adults: A Systematic Review with Meta-Analysis - Courel-Ibáñez, Javier; Vetrovsky, Tomas; Dadova, Klara; Pallarés, Jesús G; Steffl, Michal (Nutrients, 2019)
Both regular exercise training and beta-hydroxy-beta-methylbutyrate (HMB) supplementation are shown as effective treatments to delay or reverse frailty and reduce cognitive impairment in older people. However, there is very little evidence on the true benefits of combining both strategies. The aim of this meta-analysis was to quantify the effects of exercise in addition to HMB supplementation, on physical and cognitive health in older adults. Data from 10 randomized controlled trials (RCTs) investigating the effect of HMB supplementation and physical function in adults aged 50 years or older were analyzed, involving 384 participants. Results showed that HMB supplementation in addition to physical exercise has no or fairly low impact in improving body composition, muscle strength, or physical performance in adults aged 50 to 80 years, compared to exercise alone. There is a gap of knowledge on the beneficial effects of HMB combined with exercise to preserve cognitive functions in aging and age-related neurodegenerative diseases. Future RCTs are needed to refine treatment choices combining HMB and exercises for older people in particular populations, ages, and health status. Specifically, interventions in older adults aged 80 years or older, with cognitive impairment, frailty, or limited mobility are required.
Keywords: Dietary Supplements; valeráty; elderly; nutrition; resistance training; neuromuscular function; leucine; stárnutí; Exercise; Humans; Valerates; lidé; cvičení; Aging; sarcopenia; potravní doplňky